The husbandry of domestic animals in Nigeria - Oyenuga, V.A. (1967)
Describes management systems of domesticated animals in Nigeria. The animals considered include cattle, goats, sheep and poultry. Topical details on animal population, performance and physical characteristics of each species included. Future improvement on production could be achieved through crossbreeding.